Quality of effort in college activities and learning gains: A case study in China - Sun, Chengmengxue; Liang, Jingjing; Du, Ruijun; Ma, Jiani (Frontiers in Psychology, 2022)
This study investigated the mechanism between Chinese undergraduates’ quality of effort in college activities and learning gains, using the Chinese College Student Experiences Questionnaire. 2,990 undergraduates were recruited at a case Chinese university. A number of significant differences were found in this study, such as gender, grade, and type of high school differences in the quality of effort in college activities and learning gains of Chinese undergraduates. Chinese undergraduates have less interaction with teachers, lower classroom participation, and lower intellectual skills gains than their American counterparts. Quality of effort in college activities contributed more to learning gains than demographics, with different influences based on the types of college activities. These findings reveal the characteristics of the learning experience of Chinese undergraduates and relevant influential mechanisms. Recommendations for programme designers, university faculty, and undergraduates themselves were suggested.